Pengaruh Karakteristik Ceo Terhadap Manajemen Laba Akrual Dan Manajemen Laba Riil Dengan Good Corporate Governance Sebagai Variabel Moderasi - Agung Prayogi; Metiya Fatikhatur Riziqiyah (Universitas Veteran Bangun Nusantara, 2023)
The purpose of this research is to determine and analyse the effect of CEO characteristics on accrual earnings management and real earnings management with Good Corporate Governance as a moderating variable. The population of this research is the consumer goods industry sector companies listed on the Indonesia Stock Exchange for the period 2012-2021. The purposive sampling technique was used for data collection. The research data analysis technique is multiple linear regression test, interaction test and sub-group test. The findings of this research indicate that CEO narcissism, CEO gender and CEO compensation affect accrual earnings management and real earnings management. CEO tenure has no effect on accrual earnings management and real earnings management. CEO power can only affect accrual earnings management. Managerial ownership does not act as a moderator for the relationship between CEO narcissism and accrual earnings management and real earnings management. Managerial ownership is able to moderate the relationship between CEO compensation and CEO power with accrual earnings management and real earnings management. Managerial ownership does not moderate the relationship between CEO gender and CEO tenure with accrual earnings management but is able to moderate the effect of CEO gender and CEO tenure on real earnings management. Audit quality is able to moderate CEO narcissism, CEO gender, CEO compensation, CEO tenure and CEO power on earnings management. Based on the research results, company stakeholders need to be aware of the characteristics of the CEO and need to pay attention to the existence of Good Corporate Governance.